Ipsilateral fibular transfer as a salvage procedure for large traumatic tibial defects in children in an austere environment. Issue 6 (22nd July 2016) - Keenan, Andre J; Keenan, O J F; Tubb, C; M Wood, A; Rowlands, T; Christensen, S E
Abstract : Large tibial defects present a challenging scenario for the orthopaedic surgeon, particularly in the paediatric patient. Most management options, such as the vascularised fibular graft or Ilizarov technique, require microsurgical techniques or specialist equipment. In an austere environment, acute shortening or limb amputation may be most appropriate. However, limb salvage may be achieved by ipsilateral fibular transfer. In a one-stage operation, the fibular graft is harvested and either placed in the tibial defect in an intramedullary position or secured to the tibia with screws. We present two paediatric cases where this approach was used to preserve the lower limb despite extensive explosive trauma. In the first case, an 11 cm tibial defect was managed with an ipsilateral fibular graft. The graft was placed in an intercalary position proximally, with medial displacement of the ankle and fixation of the fibula as a strut graft. In the second case, a 10 cm tibial defect was managed with an ipsilateral fibular graft, using intercalary placement proximally and distally. Both children returned to weight bearing with crutches within several months of surgery. For large tibial defects, ipsilateral fibular transfer is an effective one-stage operation that represents a viable alternative to amputation in austere environments.